ATR technique, an appropriate method for determining the degree of conversion in dental giomers. (19th October 2016) - Prejmerean, Cristina; Prodan, Doina; Vlassa, Mihaela; Streza, Mihaela; Buruiana, Tinca; Colceriu, Loredana; Prejmerean, Vasile; Cuc, Stanca; Moldovan, Marioara
Abstract: Dental light-curing giomers were developed to combine the favourable properties of diacrylic resin composites (DRCs) and glass-ionomer cements (GICs) in a single material and to eliminate their inherent drawbacks. Giomers are characterized by their aesthetic appearance, high mechanical properties, adhesion to dental tissues as well as fluoride release and recharge abilities. The qualities of the giomers are greatly influenced by the level of conversion of the component resins. Infrared spectroscopy is one of the most largely used techniques for the determination of the degree of conversion in resin-based dental materials. However different results were obtained due to the performances of the used methods. The present work presents the determination of conversion degree in a series of dental copolymers and their corresponding giomers using transmission Fourier transform infrared spectroscopy (FTIR) and an attenuated total reflection technique (ATR) technique, respectively, the main aim being the study of the influence of the materials composition and of the light curing modes upon the achieved conversion in the cured giomers. Beautifil II commercial giomer was used as a control. A halogen lamp and a diode-blue LED lamp were used for the curing of the materials. The results showed that the composition of the resins greatly influenced the conversion. The highest conversions (up to 79%) were obtained in the case of the experimental giomers which contained the experimental Bis-GMA urethane analogue, followed by the Beautifil II giomer (61%) and experimental giomers based on commercial Bis-GMA (up to 50%), respectively. The resins light-cured by using the diode-blue LED lamp presented slightly higher conversions than the resins cured by halogen lamp. The study demonstrates the possibility to evaluate easily and reproducibly the conversion in light-curing composite materials with complex chemical composition and structure, particularly in the case of giomers by using the ATR technique.